1988
DOI: 10.1007/bf02648250
|View full text |Cite
|
Sign up to set email alerts
|

A componential approach to understanding reading and its difficulties in preadolescent readers

Abstract: The present study is predicated on the logic of interrelated functional information processing components as an approach to understanding reading and its difficulties in preadolescent readers. The structural equation modelling (and its variants) involved these three latent components: (a) orthographic/phonological component, (b) morphological component, and (c) sentence and paragraph comprehension component. These components were subserved by a total of ten measurable tasks, all administered on-line via the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Included in her recent findings, Carlisle (1995) found that a test of morphological production given to first graders was a stronger predictor of reading comprehension in second grade than a test of phonological awareness. In addition, Leong (1988Leong ( , 1989 has reported studies with upper elementary students whose results suggest that knowledge of derivational morphology is important for reading comprehension. In one study, of ten independent variables presumed to contribute to reading proficiency, the variable that was the most predictive of reading performance measured the student's ability to offer a derived form, given the base form of the word.…”
Section: Reading/spelling Ability and Morphological Knowledgementioning
confidence: 92%
See 1 more Smart Citation
“…Included in her recent findings, Carlisle (1995) found that a test of morphological production given to first graders was a stronger predictor of reading comprehension in second grade than a test of phonological awareness. In addition, Leong (1988Leong ( , 1989 has reported studies with upper elementary students whose results suggest that knowledge of derivational morphology is important for reading comprehension. In one study, of ten independent variables presumed to contribute to reading proficiency, the variable that was the most predictive of reading performance measured the student's ability to offer a derived form, given the base form of the word.…”
Section: Reading/spelling Ability and Morphological Knowledgementioning
confidence: 92%
“…In one study, of ten independent variables presumed to contribute to reading proficiency, the variable that was the most predictive of reading performance measured the student's ability to offer a derived form, given the base form of the word. Leong (1988) explained that derived words go beyond meaning to include morphosyntactic representation; therefore serving as a nexus linking word meaning and paragraph comprehension. Since accurate reading comprehension is the final goal of reading achievement, it behooves educators to recognize that morphological knowledge may play an increasingly important role in reading achievement as students progress through the grades, beginning as early as second grade.…”
Section: Reading/spelling Ability and Morphological Knowledgementioning
confidence: 99%
“…Grossly simplifying, there was an overall good t for the Grade 4 structure and a reasonable t for the Grade 5 structure, while the t for Grade 6 was not unambiguous. In fact, the GFI seemed to be reasonably robust for the 10-to 11-year-old groups both in the Phase 1 study (Leong, 1988) and the Phase 2 cohort (Leong, Component Processes 139 1992). The results of the two-phase, two-cohort studies of Leong seem to add to the ndings of the "orchestration" of multiple codes in word reading (Berninger, 1989).…”
Section: Phonological Morphological and Sentential Components Of Reamentioning
confidence: 92%
“…With this in mind, two developmental studies were undertaken to examine the nature of the different constituents of reading and spelling (Leong, 1988(Leong, , 1992. In these developmental studies it was posited that the latent components of phonology, morphology and simple sentence comprehension, subserved by a number of measurable indicators, and the interaction of the components may explain the reading performance of 10-to 12-year-old students in Grades 4 to 6 and may pinpoint their dif culties.…”
Section: Phonological Morphological and Sentential Components Of Reamentioning
confidence: 99%
See 1 more Smart Citation